Accountability Model for Utilization of Privilege Funds Special Region of Yogyakarta 2013-2017 - Sakir Sakir; Riska Sarofah (ARISTO, 2020)
This study describes the process of accountability of DIY special funds in realizing the prosperity of DIY society 2013-2017. Special Region of Yogyakarta is one of the regions that get the special policy in the form of asymmetric decentralization. This policy is effective since the enactment of Law Number 13 the Year 2012 on the Specialties of DIY. In particular, this regulation regulates 5 privileged affairs: the procedures for filling the positions, positions, duties and authorities of the Governor and Vice Governor, the regional government of DIY, the affairs of culture, the land affairs and spatial affairs. The hope that decentralization policy in Indonesia can improve the people's welfare significantly has not been fulfilled. This is like what happened in Yogyakarta Special Region which has special authority to manage its government affairs. However, these expectations still cannot be met well. This study aims to analyze the accountability model for the utilization of DIY privileged funds so as to provide policy recommendations to be taken. This research uses the qualitative method with data collection method with in-depth interview technique, elite interview, and documentation. The results showed that the poverty rate in DIY until March 2017 about 488.53 thousand people or about 13.02% and Ratio Gini DIY by 0.425%. This is not worth the number of privileged funds that increase each year. It is, therefore, necessary in the determination of success indicators of achievement and output in accordance with the output and outcome to be achieved. In addition, the accountability process also includes not only technical in report submission but also ensuring that process and involving the community in the planning process until accountability.